ISLAMIC COMMUNITY EMPOWERMENT THROUGH MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) DEVELOPMENT: THE STRATEGY OF MUHAMMADIYAH REGIONAL LEADERSHIP IN MEDAN - Azhari, Luthfi; Salamuddin, Salamuddin (Jurnal Al-Ijtimaiyyah, 2026)
This study examines the Islamic community empowerment strategy implemented by the Muhammadiyah Regional Leadership (Pimpinan Daerah Muhammadiyah/PDM) in developing Micro, Small, and Medium Enterprises (MSMEs) in the Mandala By Pass area of Medan City. As a religious-based community organization, Muhammadiyah plays a significant role as an agent of community economic development, particularly in addressing challenges faced by MSMEs such as limited capital access, low managerial capacity, and minimal digital technology utilization. This study employed a qualitative method with a descriptive approach. Data were collected through in-depth interviews, participatory observation, and documentation involving PDM administrators and MSME actors, and analyzed using the interactive model of Miles and Huberman, with source and method triangulation for validation. The findings reveal that the empowerment strategy was carried out systematically and participatorily across three dimensions: (1) strategic planning based on socio-economic mapping and community needs assessment; (2) sustained mentoring and guidance through management training, digital marketing, and periodic evaluation; and (3) implementation of community economic programs grounded in Islamic economic values such as honesty (ṣidq), trustworthiness (amānah), and social responsibility. This study contributes a replicable model of value-based Islamic community development led by religious organizations at the local level.